ANALISIS PERLAKUAN ZAKAT DALAM PERHITUNGAN PAJAK PENGHASILAN ORANG PRIBADI (PPh 21) PADA BADAN AMIL ZAKAT NASIONAL (BAZNAS) KOTA MAKASSAR - Aprillah, Dewi; Suarni, Agusdiwana; Salim, Agus (Jurnal Ar-Ribh, 2021)
This type of research is a comparative study that aims to discuss the comparison of zakat as a deduction for taxable tax with zakat arrangements as a direct deduction of translation tax. Data retrieval of this research refers to interviews and document techniques. The type of data consists of primary data. Based on the research that has been carried out, the conclusions from the research proposed in this study are zakat as a personal tax calculation in Baznas Makassar city in accordance with the procedures stipulated in applicable laws and regulations, zakat which is used as deduction from taxable results of individuals management both from success and distribution increases in terms of capacity and improvement and its application that increases development from year to year in which the number of ASNs that pay zakat increases every year.Keywords: Tax, Zakat Treatment and Personal Income Tax (PPh 21)